Analysis of S-Wave Propagation and Resistivity Value in Porous Medium for Conjecture Potential of Groundwater in Lempuing Village, Bengkulu City - Melly Angglena; Marzuki Marzuki; Arif Ismul Hadi (Jurnal Penelitian Pendidikan IPA, 2022)
Bengkulu city is facing groundwater problems where some of the groundwater is brackish. The study aimed to determine the structure of the subsurface layer through the propagation velocity of secondary wave (Vs) in a layer of porous medium in estimating the potential for groundwater. This research supported by resistivity data ​​and will be validated based on the depth of the well. MASW data was processed using WinMASW Professional 5.0 software to obtain a 1D profile of the Vs value, and Res2dinv software was used to obtain a 2D cross-section of the resistivity value. The results showed a decrease in the value of Vs in the porous medium layer from 133 to 358 m/s in the first path, and from 149 to 314 m/s for the second path. The decrease in the value of Vs is in the range of groundwater potential which is close to the depth of the resident's well, with the type of porous medium layer being sands and intact clays. The subsurface profile from the Vs measurement shows a good agreement with the resistivity value profile from the Geoelectric method. So, secondary wave propagation can be used in determining groundwater potential for a depth of < 10 m